Analysis of the Family's Role on the Status of Weight and Height of Children at Pelita Hati Early Childhood Education - Eny Susilowati; Heri Saputro; Prima Dewi Kusumawati; Joel Rey Ugsang Acob (Open Access Health Scientific Journal, 2022)
Background: Child health problems are a major problem in Indonesia, especially those related to nutrition in children under five. This can cause barriers to the child's height and weight. This study aimed to analyze the influence of the role of the family on the weight and height status of children.Methods: This research design is an observational quantitative research with a cross sectional approach with the focus of his research directed at analyzing the independent variable the role of the family on the dependent variable of weight and height status in children at PAUD Pelita Hati Karangrejo Tulungagung using linear regression statistical test with a sample of 35 respondents were taken by using Simple Random Sampling technique.Results: The results of the study found that almost half of the respondents had a moderate category of family roles as much as 16 respondents (45,7%). Almost half of the respondents have body weight in the normal category as much 16 respondents (45,7%) and most of the respondents have a normal height category of 20 respondents (57,1%). Results of data analysis using Test Linear Regression on the weight variable that the p-value is 0.00 0 < 0.05 then H0 is rejected and H 1 is accepted so it can be concluded that there is an influence of the role of the family on the weight status of children in PAUD Pelita Hati Karangrejo Tulungagung. Meanwhile, in the height variable, the p-value is 0.045 <0.05, so H0 is rejected and H1 is accepted , so it can be concluded that there is an influence of the role of the family on the height status of children in PAUD Pelita Hati Karangrejo Tulungagung.Conclusion: Parents can monitor their child's growth and also provide foods that are high in fiber such as fruits and vegetables, foods that contain lots of protein such as meat and tempeh, drinks that contain lots of calcium such as milk so that children can grow optimally